(untitled) (Revista Nacional de Odontología, 2021)
Endodontic treatment includes mechanical therapy combined with irrigation and disinfection techniques to remove vital pulp, non-vital pulp, and infected or necrotic pulp aiming to reduce intracanal pathogens to a level compatible with endodontic health. Infections in the root canal system are polymicrobial in which diverse microorganisms aggregated within extracellular polysaccharide matrix biofilms, therefore endodontic irrigation and mechanical debridement must need to disrupt this established microbial community and its products. Brand new clinical irrigation systems are promoted by their properties against diverse pathogenic endodontic microbiota, but their antimicrobial effectiveness is a matter of discussion. This study aimed to determine the anti-microbial properties of four common endodontic irrigation products against five ATCC strains in an in vitro test. Objective: Determine the minimum bactericidal concentration (MBC) and the minimum inhibitory concentration (MIC) of 5.25% NaOClâ, 0.12% Chlorhexidineâ, MTADâ and Qmixâ against reference strains including Aggregatibacter actinomycetemcomitans – ATCC 29522, Porphyromonas gingivalis – ATCC 33277, Candida albicans – ATCC 44858, Enteroccocus faecalis - ATCC 29212 and Enterobacter cloacae 13047. Methods and Materials: A microdilution broth test was carried out in triplicate to determine the minimum inhibitory concentration and the minimum bactericidal concentration of endodontic irrigation against specific microbial strains. Microbial viability was determined using resazurin, and microbial subcultures according to the adapted Norms of Clinical and Laboratory Standards (NCCL) - 2015. Results: C. albicans, E. faecalis and E. cloacae were the microorganisms more resistant against the microbicide action of Qmixâ and C. albicans, and E. faecalis the more resistant microorganisms against BioPure MTADâ. The BioPure MTADâ had a MIC of (1:8) against E. faecalis and C. albicans and the more susceptible bacteria were A. actinomycetemcomitans, P. gingivalis and E. cloacae, with MIC (1:8192; 1: 2048; and 1: 1024, respectively). The most resistant against QMIXâ (MIC) were E. faecalis, (1:4), followed by E. cloacae and C. albicans (1:8), and the more susceptible were P. gingivalis (1:1024), and A. actinomycetemcomitans (1:512), respectively. On the other hand, the less susceptible to Chlorhexidineâ was P. gingivalis (MIC, 75 μg/mL), followed by A. actinomycetemcomitans (MIC, 38 μg /mL), while the more susceptible were C. albicans, MIC 19 μg /mL, E. cloacae MIC 9 μg/ mL and E. faecalis MIC 4.7 μg /mL. For NaOCLâ, C. albicans (1,563 μg /mL) was the more susceptible, followed by E. cloacae, P. gingivalis and E. faecalis (781 μg/mL) and the less susceptible was A. actinomycetemcomitans (391 μg/mL). Conclusions: C. albicans, E. cloacae and E. faecalis were the more resistant strains against the endodontic irrigation products tested. The (CIM) of BioPure MTADâ performed slightly better than QMixâ. Chlorhexidineâ (0.12%) was more effective than NaOCLâ (5.25%) in inhibiting most microbial strains used. However, P. gingivalis was the less susceptible to Chlorhexidineâ, requiring 75 μg/mL for CIM. Overall, Chlorhexidineâ showed the best antimicrobial property as endodontic irrigation product in this in vitro test, therefore, this product efficacy might be proved against the complexity of biofilms in other vitro test and also at the clinical setting.